THE ROLE OF COMPETITION LAW IN REGULATING WAGE-FIXING AND NO-POACH AGREEMENTS (EU and comparative law issues and challenges series (ECLIC), 2024)
No-poach agreements and wage-fixing arrangements are increasingly assessed by national competition authorities and the European Commission as anticompetitive practices under Article 101 of the Treaty on the Functioning of the European Union (TFEU). This paper evaluates whether these agreements are sufficient to be considered anticompetitive abuses, with a focus on the European Commission’s investigation into the food delivery sector, specifically the cases involving Delivery Hero and Glovo. It explores the complexities of intra-group exemptions, where companies are treated as competitors despite belonging to the same corporate group. The paper further discusses the intersection of labor and competition law, analyzing the combined impact of these practices on labor market dynamics and competition. The paper concludes by emphasizing the importance of comprehensible enforcement mechanisms to protect labor market competition within the EU.